2014
DOI: 10.1007/s00006-014-0451-7
|View full text |Cite
|
Sign up to set email alerts
|

Connections on Cahen-Wallach Spaces

Abstract: Abstract. We systematically discuss connections on the spinor bundle of Cahen-Wallach symmetric spaces. A large class of these connections is closely connected to a quadratic relation on Clifford algebras. This relation in turn is associated to the symmetric linear map that defines the underlying space. We present various solutions of this relation. Moreover, we show that the solutions we present here provide a complete list with respect to a particular algebraic condition on the parameters that enter into the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Here C (W ) denotes the Clifford algebra of W . In [16] such connections are discussed in detail, and we will state the result in Propositions 4.1 and 4.3. In Appendix A we recall our conventions for the Clifford algebra.…”
Section: Connections and Parallel Spinorsmentioning
confidence: 97%
See 2 more Smart Citations
“…Here C (W ) denotes the Clifford algebra of W . In [16] such connections are discussed in detail, and we will state the result in Propositions 4.1 and 4.3. In Appendix A we recall our conventions for the Clifford algebra.…”
Section: Connections and Parallel Spinorsmentioning
confidence: 97%
“…In [16] we showed that pairs of this type play an essential role, when we look for flat connections. 5 From the physics point of view the three-form -or more precisely the combination Γ + sc ,d (eµ) -can be interpreted as the additional ingredient in the variation of the gravitino that comes from the curvature of the three-form potential in minimal eleven dimensional supergravity theories, see, for example, [6].…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…From [9] we know that any connection D on S that is compatible with the symmetric structure of M B is described by a pair of elements (c, d) of the Clifford algebra of V . It is given by…”
Section: Connections On the Spinor Bundlementioning
confidence: 99%